Ferroelectric Domain Wall Motion in Freestanding Single‐Crystal Complex Oxide Thin Film. Issue 4 (9th December 2019) - Bakaul, Saidur R.; Kim, Jaegyu; Hong, Seungbum; Cherukara, Mathew J.; Zhou, Tao; Stan, Liliana; Serrao, Claudy R.; Salahuddin, Sayeef; Petford‐Long, Amanda K.; Fong, Dillon D.; Holt, Martin V.
Abstract: Ferroelectric domain walls in single‐crystal complex oxide thin films are found to be orders of magnitude slower when the interfacial bonds with the heteroepitaxial substrate are broken to create a freestanding film. This drastic change in domain wall kinetics does not originate from the alteration of epitaxial strain; rather, it is correlated with the structural ripples at mesoscopic length scale and associated flexoelectric effects induced in the freestanding films. In contrast, the effects of the bond‐breaking on the local static ferroelectric properties of both top and bottom layers of the freestanding films, such as domain wall width and spontaneous polarization, are modest and governed by the change in epitaxy‐induced compressive strain. Abstract : It is found that the interfacial bond‐breaking in epitaxially grown ferroelectric perovskite thin films drastically reduces the domain wall velocity. This phenomenon is attributed to the flexoelectric effect, caused by nanoscale structural ripples induced in freestanding perovskites. This work indicates that structural and energy landscapes in freestanding perovskite films can be significantly different than those in the as‐deposited same material.